Assessment of National Policy on Education and its Implication for Poverty Eradication in Nigeria - Omorede, Christiana Kayinwaye (Journal of Research in Educational Sciences; Vol 5 No 1 (2014): JRES, Volume V, Issue 1(7), 2014DO - 10.14505/jres.v5.7.03, 2014)
This paper examines the implications of education policy in the eradication of poverty. The objectives of this study amongst others are (i) to have an in depth understanding of the concept of poverty and to determine its extent in Nigeria (ii) to assess the National policy on education in relation to the nation's philosophy and (iii) to ascertain their relevance for poverty eradication. Secondary sources were used to collect data; while the human resource capital and basic needs theories were adopted to X-ray the study. The study reveals that every responsible and responsive government has the challenge to make life better and more meaningful for its citizenry. It established a strong relationship between education and development and stressed that the topmost aim of social policies such as education, should be used to develop human beings who are capable of attacking poverty, through its provision of high skilled manpower, enhancement of income levels of individuals, thereby eradicating or at least reducing poverty level of the Nation. It also shows that limited funding in the education sector is militating against the development of education. The study concludes that education is a Sine qua non for poverty eradication and recommends that poverty eradication will be a mirage in Nigeria if there is no good governance to provide adequate funding for qualitative and quantitative infrastructure for the education sector.